2002
DOI: 10.1128/mcb.22.15.5434-5442.2002
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Escherichia coli Methionyl-tRNA Formyltransferase in Saccharomyces cerevisiae Leads to Formylation of the Cytoplasmic Initiator tRNA and Possibly to Initiation of Protein Synthesis with Formylmethionine

Abstract: Protein synthesis in eukaryotic cytoplasm and in archaebacteria is initiated with methionine, whereas, that in eubacteria and in eukaryotic organelles, such as mitochondria and chloroplasts, is initiated with formylmethionine. In view of this clear distinction, we have investigated whether protein synthesis in the eukaryotic cytoplasm can be initiated with formylmethionine, and, if so, what the consequences are to the cell. For this purpose, we have expressed in an inducible manner the Escherichia coli methion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Initiation codons, acting with an initiation tRNA, usually encode formyl methionine (fMet) in bacteria, chloroplasts, and mitochondria or methionine (Met) in archaea and the cytosol of eukaryotes (34)(35)(36). The codon wobble position is P1, where the order of usage for prokaryotes is usually AUG Ͼ GUG Ͼ UUG Ͼ CUG.…”
Section: Chain Initiation Codonsmentioning
confidence: 99%
“…Initiation codons, acting with an initiation tRNA, usually encode formyl methionine (fMet) in bacteria, chloroplasts, and mitochondria or methionine (Met) in archaea and the cytosol of eukaryotes (34)(35)(36). The codon wobble position is P1, where the order of usage for prokaryotes is usually AUG Ͼ GUG Ͼ UUG Ͼ CUG.…”
Section: Chain Initiation Codonsmentioning
confidence: 99%
“…Eubacterial and organellar nascent proteins begin with an N-formylated Met. Peptide deformylase (PDF; EC 3.5.1.88) activity is required to unmask the first Met, facilitating the action of MAP [21,22]. NME is an irreversible cotranslational mechanism, completed before the nascent polypeptide chains are fully synthesized [23].…”
Section: Introduction: What Is Nme and What Does It Do?mentioning
confidence: 99%
“…Ramesh et al [14] showed that expression of E. coli MTF in S. cerevisiae led to formylation of the cytoplasmic initiator (up to 70%) and possibly to initiation of protein synthesis with formylmethionine. The slow growth phenotype of yeast caused by expression of E. coli MTF could be rescued by co-expressing E. coli polypeptide deformylase (DEF), an enzyme that removes formyl groups from the N-terminus of proteins.…”
Section: Role Of Unique Features Of E Coli Initiator Trna Fmet In Inmentioning
confidence: 99%
“…various Halobacterial species [11]; Methanocaldococcus jannaschii; Methanococcus maripaludis [12]), yeast (Saccharomyces cerevisiae [13,14]), and mammalian cells (e.g. COS1, HEK293, HeLa cells [15][16][17][18]).…”
Section: Isolation Of Total Rna From Archaea Yeast and Mammalian Cellsmentioning
confidence: 99%